Determinants of Long-Term Durable Glycemic Control in New-Onset Type 2 Diabetes Mellitus - Kyoung Jin Kim; Ju Hee Choi; Kyeong Jin Kim; Jee Hyun An; Hee Young Kim; Sin Gon Kim; Nam Hoon Kim (Diabetes & Metabolism Journal, 2017)
BackgroundLong-term durable glycemic control is a difficult goal in the management of type 2 diabetes mellitus (T2DM). We evaluated the factors associated with durable glycemic control in a real clinical setting.MethodsWe retrospectively reviewed the medical records of 194 new-onset, drug-naïve patients with T2DM who were diagnosed between January 2011 and March 2013, and were followed up for >2 years. Glycemic durability was defined as the maintenance of optimal glycemic control (glycosylated hemoglobin [HbA1c] <7.0%) for 2 years without substitution or adding other glucose-lowering agents. Clinical factors and glycemic markers associated with glycemic durability were compared between two groups: a durability group and a non-durability group.ResultsPatients in the durability group had a higher baseline body mass index (26.1 kg/m2 vs. 24.9 kg/m2) and lower HbA1c (8.6% vs. 9.7%) than the non-durability group. The initial choice of glucose-lowering agents was similar in both groups, except for insulin and sulfonylureas, which were more frequently prescribed in the non-durability group. In multiple logistic regression analyses, higher levels of education, physical activity, and homeostasis model assessment of β-cell function (HOMA-β) were associated with glycemic durability. Notably, lower HbA1c (<7.0%) at baseline and first follow-up were significantly associated with glycemic durability (adjusted odds ratio [OR], 7.48; 95% confidence interval [CI], 2.51 to 22.3) (adjusted OR, 9.27; 95% CI, 1.62 to 53.1, respectively), after adjusting for confounding variables including the types of glucose-lowering agents.ConclusionEarly achievement of HbA1c level within the glycemic target was a determinant of long-term glycemic durability in new-onset T2DM, as were higher levels of education, physical activity, and HOMA-β.